Pengolahan Persampahan dan Bank Sampah Kelurahan Betungan Kota Bengkulu - Onsardi, Onsardi; Kusuma, Merta; Yulinda, Ade Tiara; Yuniarti, Rina; Saroni, Saparudin; Arianto, Tezar (Universitas Malikussaleh, 2024)
The implementation of this community service activity took the form of training on the use of digital marketing conducted by FEB and FKIP Biology lecturers at UM Bengkulu with community participants managing the Betungan sub-district waste bank. Previously, partners marketed waste bank handicrafts offline, namely by displaying them in the waste bank window only. Training participants are able to operate smartphones for internet access. This means that these community service partners are not completely unfamiliar with technological developments, especially the use of smartphones and social media. Based on the results of interviews, several participants have made online purchase transactions and have Instagram, Facebook and WhatsApp accounts.